Pengembangan Kompetensi ASN dari Smart ASN menuju Transformasi Digital dalam Pelayanan Publik - Gustina Theresia Lubis; Rosari Zakia Ahadi; Satria Nasution; Vip Paramartha (Journal of Management and Social Sciences, 2024)
Digital transformation has become an urgent need for the government and public sector to improve efficiency, effectiveness and quality of service to the community. The government needs to adopt concrete steps to improve ASN competency so that they can keep up with developments in information and communication technology (ICT). Implementation of the ASN competency development strategy will enable ASN to use artificial intelligence facilities for analytical purposes to improve efficiency, effectiveness and quality of public services.